Pelatihan Literasi dalam Meningkatkan Kemampuan Pemahaman Konsep Siswa SMA Kristen Payeti - Darius Imanuel Wadu; Vidriana Oktaviana Bano; Iona Lisa Ndakularak; Yohana Ndjoeroemana; Audrey Louise Makatita; Mayun Erawati Nggaba; Elsy S. H. Taunu; Yuliana Tamu Ina Nuhamara (Politeknik Kampar, 2024)
Until now, Indonesia is still in the category of worrying literacy, which is caused by the low interest in reading among Indonesian people. This is supported by a survey conducted by PISA, where Indonesia's ranking is ranked 64 out of 65 countries. In addition, a survey conducted by UNESCO also supports that the reading interest of Indonesian people is at 0.001, which means that out of 1,000 Indonesian people, only one person has a high interest in reading. This indicator should be a concern and even a warming for the Government, because it is a setback for the country in terms of human resources, especially for students. The method used in this activity is training, where students are trained to read, understand math and science problems that are contextual to life, and try to solve the problems. In addition, students are given motivation to continue to use the library as a fun place to read. Based on the results of data collection through questionnaires and interviews, we found that this activity had a positive influence on students' literacy understanding, especially among Payeti Christian High School students. The expected positive impact of this training is that it can increase students' motivation to read, especially students' understanding in understanding contextual mathematics and science problems so that it can improve students' conceptual understanding abilities well.